2019
DOI: 10.1101/757344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of Brain Tumor IDH Status using MRI and Deep Learning

Abstract: Isocitrate dehydrogenase (IDH) mutation status is an important marker in glioma diagnosis and therapy. We propose a novel automated pipeline for predicting IDH status noninvasively using deep learning and T2-weighted (T2w) MR images with minimal preprocessing (N4 bias correction and normalization to zero mean and unit variance). T2w MRI and genomic data were obtained from The Cancer Imaging Archive dataset (TCIA) for 260 subjects (120 High grade and 140 Low grade gliomas). A fully automated 2D densely connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Our model with noteworthy AUC and sensitivity may help in the above-mentioned situation. Finally, the acquired satisfactory and encouraging results are in accordance with other multi-scanner and multi-centre studies, which have reported realistic generalisable prediction rates for noninvasive IDH mutation status determination [19,56,57].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our model with noteworthy AUC and sensitivity may help in the above-mentioned situation. Finally, the acquired satisfactory and encouraging results are in accordance with other multi-scanner and multi-centre studies, which have reported realistic generalisable prediction rates for noninvasive IDH mutation status determination [19,56,57].…”
Section: Discussionsupporting
confidence: 88%
“…We claim that such a combination benefits feature extraction given the small number of samples. Model performance often degrades using multi-scanner and multi-centre cohorts, as shown by similar work using the Cancer Imaging Archive (TCIA) which studied structural images rather than DTI [56,57]. On the other hand, we have an unbalanced cohort as expected because IDH1 or IDH2 mutations are common in 70-80% of gliomas [10,29].…”
Section: Discussionmentioning
confidence: 90%